Using Internet Services to Manage Massive Evolving Information for Ubiquitous Computing Systems - Kiciman, Emre (Ubicomp 2002 Doctoral Consortium. In the Adjunct Proceedings of the Fourth International Conference on Ubiquitous Computing (Ubicomp) 2002, 2002)
A major challenge in building ubiquitous computing systems is the large variety of heterogeneous devices. Building applications that cope with this heterogeneity requires managing massive amounts of quickly evolving information, mapping among the various semantically-equivalent functionalities of devices. We advocate using Internet services to store and collect these mappings. We are implementing this hypothesis in the IMHome project, focusing on the spontaneous interaction of media creation, storage, and playback devices. To evaluate IMHome, we are developing metrics to measure the dependability of IMHome-based applications.